Monkey News: o humor de José Simão no meio virtual - Barbuio, Eduardo (2010)
In our work we analyze the construction of the humor in verbal texts of Jose Simão in posts of his personal videoblog – the Monkey News. The reason of the choice was for the sum of Jose Simão one of the most popular chronicler in the Brazilian journalistic scene and for admiring the linguistic creativity in its texts that satirize characters from the politician, social and televising national and international context and turn on controversial, boarding subjects without embarrassments. Another reason is the originality of studies involving oral texts of Jose Simão. Our research had the objective of demonstrating the humor characteristics in jokes of the oral texts of Jose Simão under the light of theoreticians of humor. Another objective of the study was to characterize the genre ―videoblog‖ based on Bakthin (2000) and Marcuschi (2005). As analysis procedure, we characterize the humor of Jose Simão based on ideas proposed by Bergson (2001), Propp (1976) and Possenti (1998) and, for the description and analysis of the jokes presented in the oral humoristic texts of Jose Simão, we used Raskin´s (1985) semantic theory of humor, also having as reference the studies of França (2006). Based on this theory, we analyzed the mechanisms of the scripts opposition, the ways of communication bona fide and non-bona fide, the humor trigger, as well as its classifications and the types of humor. The study allowed us to verify in Simão‘s oral texts the different types of triggers and humor considered by Raskin (1985), being the opposition triggers and the political humor the most recurrent type. We could also verify that the presented humoristic construction in José Simão‘s verbal texts is very similar in its written texts. We have found, in Monkey News videoblog, great proximity with talk shows and with televising reporters. There is, therefore, the approach between the Internet and the television, and a mixture of genres that had originally emerged in the televising universe, but in high speed internet connection times they are also created in virtual environments.